Effects of a Short-time health literacy promotion program (HeLPP) on biochemical factors, self-care and quality of life among rural patients with type-2 diabetes: A field trial with Solomon four-group design - Farzaneh Golboni; Hakim Ahmadzadeh; Haidar Nadrian; Towhid Babazadeh; Sarisa Najafi; Parvaneh Ghahremaninasab; Kamyar Pirehbabi; Haleh Heizomi; Hassan Mahmoodi (Tabriz University of Medical Sciences, 2024)
Background: Current evidence suggests that health literacy (HL) impacts self-care behaviors and quality of life (QOL) in patients with type 2 diabetes mellitus (T2DM). This study aimed to evaluate the impact of a short-time health literacy promotion program (HeLPP) on self-care behaviors and QOL in rural patients with type 2 diabetes. Methods: Conducted from 2018 to 2019 in Chaldoran county, Iran, this randomized controlled trial followed the Solomon four-group design. Participants included 160 rural individuals with T2DM, who were divided into two intervention (A and C) and two control (B and D) groups. Pre-tests were conducted for intervention group A and control group B, with post-tests administered to all groups at three and six months. Interventions, consisting of five training sessions lasting 45 to 55 minutes, were planned and executed based on pre-test analyses. Primary outcomes were QOL and self-care behaviors, and secondary outcomes were glycated hemoglobin (HbA1c), HL and patients' awareness of the disease. Results: Prior to the intervention, there was no significant difference in awareness, HL, self-care behaviors, HbA1c, and QOL between intervention group A and control group B (P>0.05). However, at three and six months after the educational program, intervention group A exhibited significantly increased average scores in awareness, HL, self-care behaviors, and QOL, along with reduced HbA1c levels (P<0.05) compared to control group B. No interaction was detected between the pre-test and the primary and secondary outcome scores after intervention. Conclusion: Implementing intervention programs like HeLPP focusing on enhancing practical HL and empowering T2DM patients seems to be promising in improving patients' self-care behaviors and QOL, while reducing their HbA1c levels. Trial Registration: Identifier: IRCT20131116015422N7; https://irct.behdasht.gov.ir/trial/35569.